Tinjauan Penerapan Kebijakan Industri Ayam Ras : Antara Tujuan dan Hasil - Yusmichad Yusdja; Nyak Ilham; Rosmijati Sajuti (Forum penelitian Agro Ekonomi, 2004)
EnglishThe government policy related to development of layer and broiler industry began in 1970 through foreign investment. In the same year the government approved development of broiler and layer hatchery industry from Japan and United States. This policy was followed-up by broiler and layer farms policy in 1980 that limited economic scales of the farms. The objective of the policy is to create employment as many as possible for smallholders backed up by Livestock Bill No. 67. After 20 years of the Bill enactment, however, the policy was ineffective and encouraged the big scale farms to arrive at uncontrollable growth. In 1996, namely right before economic crisis took place, layer and broiler industry were dominated by the big scale farms and the independent smallholders did not exist anymore. This paper aims to describe the policies related to layer and broiler industry development since 1979 to 2003. This experience is important as the knowledge in order to develop the other commodities such as dairy cows, native chicken, food crops, and estate crops which, so far, are still chained up in the smallholders protecting policies.IndonesianKebijaksanaan pemerintah menyangkut pengembangan industri ayam ras dimulai tahun 1970 melalui kebijakan penanaman modal asing (PMA). Pada tahun tersebut disetujui pengembangan pembibitan ayam ras dari negara Jepang dan Amerika Serikat. Kebijakan ini disusul dengan kebijakan budidaya tahun 1980 yang mengatur pembatasan skala usaha ayam ras. Tujuan kebijakan tersebut adalah untuk menyediakan lapangan kerja sebanyak-banyaknya bagi rakyat  dengan dukungan UU Peternakan No 67.  Namun setelah 20 tahun berlangsung, ternyata kebijakan ini tidak berhasil efektif  bahkan mendorong percepatan pertumbuhan skala besar yang semrawut.  Pada tahun 1996 sesaat sebelum krisis ekonomi, industri ayam ras dikuasai oleh peternak skala besar. Usaha rakyat dalam bentuk mandiri dapat dikatakan tidak ada lagi. Tujuan tulisan ini  adalah untuk memaparkan perjalanan kebijakan pengembangan industri ayam ras dari tahun 1979 sampai tahun 2003. Pengalaman ini penting sebagai pengetahuan dalam rangka mengembangkan komoditas lain seperti sapi perah, ayam buras dan  tanaman pangan, maupun perkebunan yang sampai saat ini terbelenggu dalam kebijakan perlindungan usaha rakyat.